2021
DOI: 10.1177/00033197211029094
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index Is a Predictor of Contrast-Induced Nephropathy in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: We evaluated the predictive value of admission systemic immune-inflammation index (SII) for the risk of contrast-induced nephropathy (CIN) in patients with ST-segment elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI). The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and SII (platelet × NLR) levels were calculated in 1621 consecutive patients with STEMI. The relationship of these parameters with CIN development within 72 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 38 publications
1
37
1
Order By: Relevance
“…They reported that the patients with CIN had increased hsCRP, glucose, total cholesterol, NLR, and SII levels compared with the patients without CIN and SII was an independent predictor of CIN [51]. Recently, Ozturk et al [25] have concluded that SII was markedly elevated in patients with STEMI undergoing primary PCI and independently predicted CIN. Also, CRP, eGFR, and baseline creatinine were associated with CIN in their study [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the patients with CIN had increased hsCRP, glucose, total cholesterol, NLR, and SII levels compared with the patients without CIN and SII was an independent predictor of CIN [51]. Recently, Ozturk et al [25] have concluded that SII was markedly elevated in patients with STEMI undergoing primary PCI and independently predicted CIN. Also, CRP, eGFR, and baseline creatinine were associated with CIN in their study [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ozturk et al [25] have concluded that SII was markedly elevated in patients with STEMI undergoing primary PCI and independently predicted CIN. Also, CRP, eGFR, and baseline creatinine were associated with CIN in their study [25]. In addition, Bagcı et al [52] conducted a novel study to assess the relationship between SII and development of CIN in patients with STEMI who underwent primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The prognostic value of SII in many clinical conditions such as cancer, contrastinduced nephropathy, pulmonary embolism, and coronary artery disease has been demonstrated. 14,[33][34][35] Esenboga et al determined the relationship between no-reflow and SII in patients who underwent primary percutaneous coronary intervention (PCI) due to ST-elevation myocardial infarction (STEMI). 36 Yang et al showed an association between increased SII values and poor CV outcomes after PCI in coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,17 In addition to CRP, cystatin-C, procalcitonin, NLR, PLR, MPVLR, and systemic immune-inflammation index may be independent predictors of CIN. 7,10,[18][19][20] A recent study, which investigated the relationship between plasma endothelial microparticles and CIN in patients who underwent CAG, demonstrated that cystatin-C, high-sensitivity CRP, and uric acid were significantly higher in patients with CIN than ones without CIN. 8 The researchers found that elevated microparticles in CIN patients correlated with interleukin-6 and high-sensitivity CRP, and reported that high cystatin-C, uric acid, and N-terminal pro-brain natriuretic peptide were the predictors of CIN rather than high-sensitivity CRP.…”
Section: Discussionmentioning
confidence: 99%